Twenty-year analysis of age and type of surgical treatment in a woman with breast cancer in University Hospital Dubrava: a retrospective study - Marina Plantak; Ivan Milas; Josip Jaman; Krešimir Grgat; Filip MIkulić; Rado Žic (Libri Oncologici, 2024)
Introduction: According to the World Health Organization, breast cancer remains a pervasive global health problem, affecting millions of women each year and posing significant challenges to health systems worldwide. Understanding epidemiology and therapeutic methods, especially in regional contexts such as Croatia, is key to optimizing patient care. The etiology of the disease is unknown, but there are risk factors such as family history, hormonal influence, lifestyle, and exposure to radiation and certain chemicals. Early diagnosis, through regular mammography examinations, is crucial in successful treatment and survival. Objective: To retrospectively analyze age and types of surgical treatment. Methods: The research was conducted at the Dubrava Clinical Hospital. Patients surgically treated at Dubrava Clinical Hospital with breast cancer in the period from January 1, 2004, to December 31, 2023, were analyzed. Results: 3710 patients were analyzed. The mean age is 57.41 ± 13.04 (95% CI 56.99 – 57.83). The median age is 57 years. There were 1728 breast-conserving surgeries, 1015 mastectomies without reconstruction, 363 mastectomies with body tissue breast reconstruction, and 604 mastectomies with direct-to-implant reconstruction. Conclusion: The hypothesis that the average age of patients operated on with a diagnosis of breast cancer is between 35 and 55 years was rejected, and the hypothesis that more breast-conserving than radical surgical procedures were performed was rejected. The hypothesis that the number of direct-to-implant reconstructions is greater than the number of reconstructions with autologous tissue has been accepted.